The Impact of Career Development and Job Satisfaction on Lecturer Performance - Bahri, Samsul; Ashlan, Said; Mulyono, Hardi (Migration Letters, 2023)
Purpose: This research aims to examine and analyze the influence of career development and job satisfaction on lecturer performance. Design/methodology/approach: The research instrument uses a questionnaire with a Likert scale. The research data was processed and analyzed using path analysis. The population for this research was 246 lecturers. Sampling was carried out using the proportional random sampling technique with a sample size of 152 people. Findings: The results of the analysis show that there is a direct influence of career development on lecturer performance with a path coefficient of 0.228, and there is a direct influence of job satisfaction on lecturer performance with a path coefficient of 0.278. Based on the results of the analysis, various efforts need to be made to improve lecturer performance, including increasing career development and job satisfaction. Research limitations and mplications: This research is only limited to the variables of career development, job satisfaction, and lecturer performance at Al Washliyah Muslim Nusantara University, and the research findings are too narrow and cannot be used as a standard reference for career development, job satisfaction, and lecturer performance at other work institutions. Practical implications: Career development, job satisfaction, and lecturer performance can increase if given a career opportunity that suits capacity and productivity, an adequate salary, friendly co-workers, superior competence, and a harmonious work environment.